2020
DOI: 10.1074/jbc.ra120.013923
|View full text |Cite
|
Sign up to set email alerts
|

A trade-off switch of two immunological memories in Caenorhabditis elegans reinfected by bacterial pathogens

Abstract: Recent studies have suggested that innate immune responses exhibit characteristics associated with memory linked to modulations in both vertebrates and invertebrates. However, the diverse evolutionary paths taken, particularly within the invertebrate taxa, as should lead to similarly diverse innate immunity memory processes. Our understanding of innate immune memory in invertebrates primarily comes from studies of the fruit fly Drosophila melanogaster, the generality of which is unclear. Caenorhabditis elegans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…If parameters within a host are correlated across bacterial taxa, positive correlations can arise simply due to fast-growing species growing quickly together. It is likewise plausible that negative correlations could arise due to differences between hosts due to parameter anti-correlations, for example if an immune response that suppresses one bacterial taxon precludes activation of responses that are effective against a second ( Yan et al, 2020 ; Zhang et al, 2021 ). Ecologically, this would produce a sort of Moran effect ( Cazelles and Boudjema, 2001 ), where correlations among non-interacting units emerge due to correlations between environmental variables.…”
Section: Resultsmentioning
confidence: 99%
“…If parameters within a host are correlated across bacterial taxa, positive correlations can arise simply due to fast-growing species growing quickly together. It is likewise plausible that negative correlations could arise due to differences between hosts due to parameter anti-correlations, for example if an immune response that suppresses one bacterial taxon precludes activation of responses that are effective against a second ( Yan et al, 2020 ; Zhang et al, 2021 ). Ecologically, this would produce a sort of Moran effect ( Cazelles and Boudjema, 2001 ), where correlations among non-interacting units emerge due to correlations between environmental variables.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, an increasing body of evidence indicates that, after priming by prior pathogenic exposure, plants and invertebrates that lack adaptive immunity display memory traits that afford them protection against subsequent infections. [6][7][8][9][10][11] Interestingly, despite vertebrates developing further down the line from these ancient precursors, innate immune memory mechanisms appear to have been conserved throughout the evolutionary process, independently of the emergence of adaptive immunity. 12 Over the past two decades, these observations were further reinforced by an increasing number of studies that described the mechanisms enabling innate immune responses to exhibit adaptive traits that can be modulated by previous encounters with microbial products.…”
Section: Innate Immune Memory From An E Volutionary Per S Pec Tivementioning
confidence: 99%
“…As adaptive immunity is present only in vertebrates, which include at most 3% of living species, it is challenging to assume that the remaining 97% of all organisms do not possess some sort of immunological memory. Indeed, an increasing body of evidence indicates that, after priming by prior pathogenic exposure, plants and invertebrates that lack adaptive immunity display memory traits that afford them protection against subsequent infections 6‐11 . Interestingly, despite vertebrates developing further down the line from these ancient precursors, innate immune memory mechanisms appear to have been conserved throughout the evolutionary process, independently of the emergence of adaptive immunity 12 .…”
Section: Innate Immune Memory From An Evolutionary Perspectivementioning
confidence: 99%
“…Another study showed that snails, Biomphalaria glabrata , primed with its compatible sympatric parasite, Schistosoma mansoni , completely resisted infection when challenged a second time with the same parasite 18 . In addition, immune memory has been broadly observed in numerous different invertebrate species such as the silk moth Bombyx mori , roundworm Caenorhabditis elegans , and mosquito Anopheles gambiae 19–21 . Lanz‐Mendoza et al 22 summarized the studies of invertebrate immune memory in a comprehensive review.…”
Section: Innate Immune Memory Among Different Speciesmentioning
confidence: 99%
“…18 In addition, immune memory has been broadly observed in numerous different invertebrate species such as the silk moth Bombyx mori, roundworm Caenorhabditis elegans, and mosquito Anopheles gambiae. [19][20][21] Lanz-Mendoza et al 22 summarized the studies of invertebrate immune memory in a comprehensive review.…”
Section: Innate Immune Memory Among Different Speciesmentioning
confidence: 99%